Ixodes scapularis does not harbor a stable midgut microbiome. Issue 11 (November 2018) - Ross, Benjamin; Hayes, Beth; Radey, Matthew; Lee, Xia; Josek, Tanya; Bjork, Jenna; Neitzel, David; Paskewitz, Susan; Chou, Seemay; Mougous, Joseph
Abstract Hard ticks of the order Ixodidae serve as vectors for numerous human pathogens, including the causative agent of Lyme DiseaseBorrelia burgdorferi . Tick-associated microbes can influence pathogen colonization, offering the potential to inhibit disease transmission through engineering of the tick microbiota. Here, we investigate whetherB. burgdorferi encounters abundant bacteria within the midgut of wild adultIxodes scapularis, its primary vector. Through the use of controlled sequencing methods and confocal microscopy, we find that the majority of field-collected adultI. scapularis harbor limited internal microbial communities that are dominated by endosymbionts. A minority ofI. scapularis ticks harbor abundant midgut bacteria and lackB. burgdorferi . We find that the lack of a stable resident midgut microbiota is not restricted toI. scapularis since extension of our studies toI. pacificus, Amblyomma maculatum, andDermacentor spp showed similar patterns. Finally, bioinformatic examination of theB. burgdorferi genome revealed the absence of genes encoding known interbacterial interaction pathways, a feature unique to theBorrelia genus within the phylum Spirochaetes. Our results suggest that reduced selective pressure from limited microbial populations within ticks may have facilitated the evolutionary loss of genes encoding interbacterial competition pathways fromBorrelia .